AB1298 Comparison of ICG-enhanced optical imaging to low-field MRI and musculoskeletal ultrasound in patients with early rheumatoid arthritis. (23rd January 2014) - Ohrndorf, S.; Krohn, M.; Werner, S.G.; Bahner, M.; Schirner, M.; Reiche, B.E.; Schneider, S.; Braum, L.; Burmester, G.R.; Hamm, B.; Hermann, K.-G.; Backhaus, M.
Abstract : Background: Fluorescence optical imaging (FOI) is a novel imaging technology. It detects hypervascularisation of inflamed joints and tissues in both hands using indocyanine green (ICG) as fluorophore. Objectives: In this study, FOI was compared to low-field MRI and musculoskeletal ultrasound (US) in patients with early rheumatoid arthritis (RA). Methods: Thirteen patients (9 female; mean age 54±15 yrs, range 26-75) with the diagnosis of early RA were enrolled. Low-field MRI (under application of 0.2 mmol/kg BW Dotarem®) and US (grey-scale (GSUS) as well as power-Doppler (PDUS) mode) of the clinically more affected hand were performed. Both methods were evaluated according to the OMERACT criteria. After informed consent, all patients were examined by the FOI device Xiralite© (mivenion GmbH, Berlin) using ICG as fluorophore (ICG-Pulsion® 0.1 mg/kg BW bolus I.V., 6 minutes examination time). Images were interpreted in three defined phases of increased signal intensity (ISI) in the finger tips: early (P1, prior to strong ISI in the finger tips), intermediate (P2, during ISI in the finger tips), and late phase (P3, after decreasing of ISI in the finger tips) [1]. Sensitivity and specificity for synovitis were calculated using MRI as reference. Furthermore, interclass correlation coefficients (ICC) were calculated between all three imaging methods. Results: In total, 104 joints (MCP n=52, PIP n=52) were evaluated. For all finger joints, FOI reached a sensitivity of 88% and specificity of 57% using MRI as reference. In detail, sensitivity of 70% and specificity of 81% was calculated for the MCPs (n=52), and sensitivity of 96% and specificity of 41% for the PIPs (n=52) (Table 1 ). The ICCs between MRI and FOI were 0.77 for the MCPs and 0.79 for the PIPs. The ICCs between US and FOI were 0.79 for the MCPs and 0.73 for the PIPs (Table 2 ). Conclusions: With MRI as reference, the novel FOI method seems to be very sensitive in the detection of synovitis, but not very specific. There was a high sensitivity especially for the PIP joint evaluation, with poor specificity, though. In contrast, MCP joint evaluation by FOI was much more specific. There were comparable good correlations between FOI and MRI as well as between FOI and US. Hence, FOI might be a helpful tool in the screening of patients with suspected early RA. References: Werner SG, Langer EH, Ohrndorf S, et al. Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology.Ann Rheum Dis. 2011 Oct 12. [Epub ahead of print] Disclosure of Interest: S. Ohrndorf Grant/Research support from: Arthromark Research Support, M. Krohn: None Declared, S. Werner Grant/Research support from: Pfizer Research Support, M. Bahner: None Declared, M. Schirner: None Declared, B. Reiche: None Declared, S. Schneider: None Declared, L. Braum: None Declared, G. Burmester: None Declared, B. Hamm: None Declared, K.-G. Hermann: None Declared, M. Backhaus Grant/Research support from: Pfizer Research Support